How Boeing reframed its supply chain to build the dreamliner - Russo, J. Edward (Henry Stewart Talks, 2016)
This case study examines how Boeing used the tactic of ‘reframing’ to galvanize a new relationship with its supply chain for the development of the Dreamliner aircraft—by framing them as Partners rather than suppliers.